Coupling of ryanodine receptor 2 and voltage-dependent anion channel 2 is essential for Ca2+ transfer from the sarcoplasmic reticulum to the mitochondria in the heart - Min, Choon Kee; Yeom, Dong Rim; Lee, Kyung-Eun; Kwon, Hye-Kyeong; Kang, Moonkyung; Kim, Yeon-Soo; Park, Zee Yong; Jeon, Hyesung; Kim, Do Han (PORTLAND PRESS LTD, 2012)
The structural proximity and functional coupling between the SR (sarcoplasmic reticulum) and mitochondria have been suggested to occur in the heart. However, the molecular architecture involved in the SR-mitochondrial coupling remains unclear. In the present study, we performed various genetic and Ca2+-probing studies to resolve the proteins involved in the coupling process. By using the bacterial 2-hybrid, glutathione transferase pull-down, co-immunoprecipitation and immunocytochemistry assays, we found that RyR2 (ryanodine receptor type 2), which is physically associated with VDAC2 (voltage-dependent anion channel 2), was co-localized in SR-mitochondrial junctions. Furthermore, a fractionation study revealed that VDAC2 was co-localized with RyR2 only in the subsarcolemmal region. VDAC2 knockdown by targeted short hairpin RNA led to an increased diastolic [Ca2+] (calcium concentration) and abolishment of mitochondrial Ca2+ uptake. Collectively, the present study suggests that the coupling of VDAC2 with RyR2 is essential for Ca2+ transfer from the SR to mitochondria in the heart.
Keywords: CALCIUM SIGNAL TRANSMISSION; ENDOPLASMIC-RETICULUM; ER; IDENTIFICATION; INCREASES; SKELETAL; RELEASE; CELLS